Evolution of TP53 abnormalities during CLL disease course is associated with telomere length changes - Olbertova, Helena; Plevova, Karla; Pavlova, Sarka; Malcikova, Jitka; Kotaskova, Jana; Stranska, Kamila; Spunarova, Michaela; Trbusek, Martin; Navrkalova, Veronika; Dvorackova, Barbara; Tom, Nikola; Pal, Karol; et al. (BMC cancer, 2022)
BACKGROUND: Telomeres are protective structures at chromosome ends which shorten gradually with increasing age. In chronic lymphocytic leukemia (CLL), short telomeres have been associated with unfavorable disease outcome, but the link between clonal evolution and telomere shortening remains unresolved. METHODS: We investigated relative telomere length (RTL) in a well-characterized cohort of 198 CLL patients by qPCR and focused in detail on a subgroup 26 patients who underwent clonal evolution of TP53 mutations (evolTP53). In the evolTP53 subgroup we explored factors influencing clonal evolution and corresponding changes in telomere length through measurements of telomerase expression, lymphocyte doubling time, and BCR signaling activity. RESULTS: At baseline, RTL of the evolTP53 patients was scattered across the entire RTL spectrum observed in our CLL cohort. RTL changed in the follow-up samples of 16/26 (62%) evolTP53 cases, inclining to reach intermediate RTL values, i.e., longer telomeres shortened compared to baseline while shorter ones prolonged. For the first time we show that TP53 clonal shifts are linked to RTL change, including unexpected RTL prolongation. We further investigated parameters associated with RTL changes. Unstable telomeres were significantly more frequent among younger patients (P = 0.032). Shorter telomeres were associated with decreased activity of the B-cell receptor signaling components p-ERK1/2, p-ZAP-70/SYK, and p-NFκB (P = 0.04, P = 0.01, and P = 0.02, respectively). CONCLUSIONS: Our study revealed that changes of telomere length reflect evolution in leukemic subclone proportion, and are associated with specific clinico-biological features of the explored cohort.
Keywords: TP53; Male; mutace; telomerasa; signální transdukce; Chronic Lymphocytic Leukemia; mužské pohlaví; nádorový supresorový protein p53; Signal Transduction; klonální evoluce; BCR signaling; Leukemia, Lymphocytic, Chronic, B-Cell; Proto-Oncogene Proteins c-bcr; lidé; Telomerase; Clonal evolution; ženské pohlaví; Humans; telomery; Clonal Evolution; Mutation; Female; protoonkogenní proteiny c-bcr; chronická lymfatická leukemie; lidé středního věku; Tumor Suppressor Protein p53; Telomere; Middle Aged